A biblical Hebrew reference grammar - Van der Merwe, C. H. J.; Naudé, J. A.; Kroeze, Jan, 1958- (England: Sheffield academic press, 2000)
"This new and fully revised edition of the A Biblical Hebrew Reference Grammar serves as a user-friendly and up-to-date source of information on the morphology, syntax, semantics and pragmatics of Biblical Hebrew verbs, nouns and other word classes (prepositions, conjunctions, adverbs, modal words, negatives, focus particles, discourse markers, interrogatives and interjections). It also contains one of the most elaborate treatments of Biblical Hebrew word order yet published in a grammar. Compiled by authors with extensive experience in the teaching of Hebrew, the text is rendered both easily accessible and a fascinating examination of the language, building upon the initial publication by incorporating up-to-date developments in the study of the Hebrew Bible. This grammar will be of service both to students who have completed an introductory or intermediate course in Biblical Hebrew, and also to more advanced scholars seeking to take advantage of traditional and recent descriptions of the language that go beyond the basic morphology of Biblical Hebrew"--
Includes bibliographical references and index.
Keywords: Hebrew language -- Grammar